TATHBĪQU THARĪQAT AL TAQLĪD WA AL TAHFĪZ LI TARQIYAT HIFZ AL MUFRADᾹT AL THULLᾹB BI AL MADRASAH AL TSANᾹWIYAH AL HUKŪMIYAH 1 BATANG HARI JAMBI - Mizan, Khairul; Musdalipa, Musdalipa (STIQ Amuntai, 2023)
Using appropriate methods in the teaching and learning process can make it easier for teachers to convey the knowledge they have. The proper technique for learning vocabulary is mimicry and memorization. This method is used by teachers at MTSN 1 Batang Hari Jambi. the application of this method is combined with the use of image media. Therefore, this research aims to analyze the application of the mimicry and memorization method in vocabulary learning, with the aim of understanding the application of the mimicry and memorization method in vocabulary learning at MTSN 1 Batang Hari, the supporting and inhibiting factors, and the impact of its application. This research is qualitative research with a descriptive approach. The data in this research was collected using three techniques, namely observation, interviews, and documentation. The data was analyzed using the Miles and Huberman model. The results of this research show that the application of this method is carried out in several ways, namely: the teacher reads the vocabulary several times by pointing to the picture on the whiteboard, and the students are only asked to listen after the students can understand the language then the teacher rereads it and is followed by all the students, after The teacher asks several students to read and is followed by other students and the teacher slowly covers the vocabulary and pictures on the whiteboard until the students have memorized them. The application of this method is supported by several factors, namely competent teachers, student focus, student activities, and learning media. Apart from that, there are inhibiting factors, namely facilities and infrastructure, student competence, and interests. Applying this method has a positive impact on vocabulary mastery and learning motivation. However, it has a partial effect on student learning outcomes.